Konsep SRA (Sekolah Ramah Anak) Dalam Membentuk Budaya Islami di Sekolah Dasar - Subur, Subur; Nugroho, Irham; Nanang Qasim, Muhammad (Universitas Muhammadiyah Magelang, 2019)
This research is titled Implementation of child friendly schools in realizing school culture in SDN Geger Tegalrejo which aims to find out whether the school has implemented child friendly schools in whole or in part and to find out the school culture which is the result of the implementation of child friendly schools. The method used in this research is descriptive qualitative which will describe how the implementation of child friendly schools in SDN Geger Tegalrejo. Data collection techniques through observation, documentation, interviews and questionnaires. Data analysis method uses descriptive method. The implementation of child friendly schools in SDN Geger Tegalrejo is in accordance with the indicators of child friendly schools and refers to the classification standards of child friendly schools that have been declared by the ministry of education and culture based on the facts contained in the field. even though SDN Geger Tegalrejo has not implemented the child friendly school as a whole, it has carried out most of the child friendly school implementation for its students. Some of the school culture in SDN Geger Tegalrejo has reflected the culture of a child-friendly school, to support and realize child friendly schools.